The encyclopedia of elder care : the comprehensive resource on geriatric and social care - Capezuti, Liz; Siegler, Eugenia L.; Mezey, Mathy Doval (Springer Pub., 2008)
Focuses on the notions of how to care for the elderly patient. This encyclopedia includes entries on: clinical symptoms and treatments of common and chronic diseases; healthcare policy issues; screening tools; tests of psychological and physical fitness; health maintenance; and medicare. It also provides information on assisted living.